Kolme toivetta - Karila, Katja; Haapakoski, Henri; Heino, Jari (basisti); Lintonen, Pinja; Lunkka, Taisto; Nieminen, Jari; Rissanen, Pasi ([kustantaja tuntematon], 2015)
3 kappaletta.
Keywords: Karila, Katja : EP:t